(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article analyzes the pedagogical views of Sadriddin Ayni, his educational activities within the Jadid movement, and his advanced ideas related to the process of education and upbringing. Ayni paid great attention to enlightening the people, reforming school education, updating national curricula, and educating the younger generation as perfect individuals. The scientific and pedagogical principles presented in his works remain relevant in today’s educational system and play an important role in ensuring a personal approach, creativity, and the harmony of national and universal values. The article highlights the ways of applying Ayni’s pedagogical ideas in the modern educational process, as well as their effectiveness and practical significance.